I'm not afraid of GDPI : group discussion and personal interview - Varshney, Tuhina Anukul (Pearson India Education Services, 2016)
In today's cut throat competitive world, an enhanced personality, excellent communication and GDPI skills are essential facets of job seeking candidates to land the best jobs. I'm Not Afraid of GDPI, 2e comprehensively deals with every aspect of the hiring process and personal grooming required to be successful. Divided in two parts, part one guides the reader through the entire ion sequence starting with strong pre-preparation to group discussions and through to the final interview. Part two helps in laying a solid foundation for an attractive personality which will be yours for life, right from a confident mindset to a winning attitude, polished body-language to acquiring 'officer-like qualities'.